FAKTOR-FAKTOR YANG MEMENGARUHI PERSEPSI WAJIB PAJAK TERHADAP TINDAKAN PENGGELAPAN PAJAK - THERESA VALENTIA; Meinie Susanty (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to obtain empirical evidence of the impact of tax system, tax rates, tax sanctions, justice, discrimination, tax audits, and understanding the taxation on taxpayers’ perseptions of tax evasion. The population in this study is an individual taxpayer registered at the Tax Office in DKI Jakarta area. The sample method used in this study is the convenience sampling method by distributing questionnaires using google form and then processing it with multiple linear regression analysis. The number of samples that match the research criteria is 104 respondens. The result of this study indicate that tax system, discrimination, and tax audits have impact on tax evasion and tax rates, tax sanctions, justice, and understanding the taxation have no impact on tax evasion.